The Influence of Brand Image, E-Service Quality, and Perceived Ease of Use on Customer E-Loyalty in Netflix Streaming Services - Tanuwidjaya, Dennis Prayudha; Imaningsih, Erna Sofriana (Archives of Business Research, 2025)
This study aims to analyze the influence of brand image, e-service quality, and perceived ease of use on customer e-loyalty toward Netflix streaming services. The subjects of this research are individuals who have subscribed to Netflix services for at least two months and reside in the Greater Jakarta area (Jabodetabek), Indonesia. The sample consists of 180 respondents selected using purposive sampling. The research approach employs Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, using SmartPLS 3 as the analytical tool. The results indicate that brand image, e-service quality, and perceived ease of use have a positive and significant effect on customer e-loyalty toward Netflix streaming services.